2014
DOI: 10.1007/s00253-013-5463-z
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification using interfacial assembly of the Streptomyces chaplin proteins

Abstract: The chaplin proteins are instrumental in the formation of reproductive aerial structures by the filamentous bacterium Streptomyces coelicolor. They lower the water surface tension thereby enabling aerial growth. In addition, chaplins provide surface hydrophobicity to the aerial hyphae by assembling on the cell surface into an amphipathic layer of amyloid fibrils. We here show that mixtures of cell wall-extracted chaplins can be used to modify a variety of hydrophilic and hydrophobic surfaces in vitro thereby c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
4
17
0
1
Order By: Relevance
“…It is also notable that a number of other biological surface structures are constructed out of thin layers of selfassembling components such as the hydrophobins and chaplins of filamentous fungi and streptomyces (Gebbink et al, 2005) and bacterial S-layers . These proteins also hold promise for biotechnological applications (Hektor and Scholtmeijer, 2005;Ekkers et al, 2014;Sleytr et al, 2014).…”
Section: Role Of Self-assembly In Spore Coat Constructionmentioning
confidence: 99%
“…It is also notable that a number of other biological surface structures are constructed out of thin layers of selfassembling components such as the hydrophobins and chaplins of filamentous fungi and streptomyces (Gebbink et al, 2005) and bacterial S-layers . These proteins also hold promise for biotechnological applications (Hektor and Scholtmeijer, 2005;Ekkers et al, 2014;Sleytr et al, 2014).…”
Section: Role Of Self-assembly In Spore Coat Constructionmentioning
confidence: 99%
“…This layer, which apparently forms the same mosaic as that found on aerial spores, renders the surface of spores hydrophobic. Recent evidence indicates that chaplins self-assemble into an asymmetric fibrillar membrane when confronted with a hydrophobichydrophilic interface (Bokhove et al, 2013;Ekkers, Claessen, Galli, & Stamhuis, 2014). The chaplin proteins form the main building blocks of the rodlet layer, by assembling into thin fibrils that are aligned by the rodlin proteins into wild-type rodlets .…”
Section: Surface Modification Of Streptomyces Sporesmentioning
confidence: 99%
“…However, the long chaplins ChpA-C were not detected, presumably due to their covalent coupling to the peptidoglycan. In vitro experiments using mixtures of monomeric chaplins have demonstrated that these proteins have a strong propensity to self-assemble into an amphipathic membrane when confronted with a hydrophobic-hydrophilic interface [ 15 , 16 ]. The hydrophobic side of this membrane is characterized by small 4–6 nm-wide fibrils that are very similar in appearance to the fibrils that are observed on the surface of spores.…”
Section: Functional Amyloid Proteins In Streptomyces Coementioning
confidence: 99%
“…How can this behavior be explained? The assembly of chaplins into an amphipatic amyloidal membrane may be a two-step process [ 16 ]. Initially, monomers accumulate at the water–air interface, leading to the formation of an intermediate, non-amyloidal membrane with high surface activity.…”
Section: Functional Amyloid Proteins In Streptomyces Coementioning
confidence: 99%
See 1 more Smart Citation